2021
DOI: 10.1002/jpen.2209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early nutrition route in patients receiving extracorporeal membrane oxygenation: A retrospective cohort study

Abstract: Background: Early nutrition management in patients receiving extracorporeal membrane oxygenation (ECMO) remains controversial. Despite its potentially beneficial effect, enteral nutrition (EN) could be associated with gastrointestinal (GI) complications. Total daily energy requirements remain difficult to achieve with ECMO support.Analysis of nutrition practices could improve nutrition management of this particular population. Methods:A monocentric retrospective study of patients requiring ECMO in a cardiac su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…GI intolerance is a common complication associated with EN which influences the decision on route of nutritional support. Gastrointestinal (GI) intolerance has been reported in 53% of ECMO patients receiving EN [49]. However, there is no significant difference in the incidence of total GI complications when comparing EN to non-EN groups of ECMO patients.…”
Section: Route Of Nutritional Support: Oral Versus Enteral Versus Par...mentioning
confidence: 99%
See 1 more Smart Citation
“…GI intolerance is a common complication associated with EN which influences the decision on route of nutritional support. Gastrointestinal (GI) intolerance has been reported in 53% of ECMO patients receiving EN [49]. However, there is no significant difference in the incidence of total GI complications when comparing EN to non-EN groups of ECMO patients.…”
Section: Route Of Nutritional Support: Oral Versus Enteral Versus Par...mentioning
confidence: 99%
“…As ECMO patients typically present with severe critical illnesses or advanced chronic illnesses which require complex care plans, low prioritization of nutritional support may lead to delayed initiation [49]. Thus, randomized clinical trials corroborating the observed mortality benefit of early EN would raise the level of evidence supporting this practice and heighten prioritization of nutritional support earlier during the ECMO course.…”
Section: Andandmentioning
confidence: 99%
“…Moreover, this MNT strategy might also be beneficial to attenuate muscle wasting and ICU‐acquired weakness 11,40,41 . On the contrary, early EN may be associated with an increased risk of feeding intolerance, which includes nausea and vomiting with pulmonary aspiration, pneumonia, and—in the context of high‐dose vasopressors—nonocclusive mesenteric ischemia and bowel necrosis 8,42,43 . Patients receiving ECMO may require frequent procedures leading to EN interruptions, 13 which may contribute to macronutrient and micronutrient deficiencies 7 …”
Section: Guidance On Timing and Route Of Mntmentioning
confidence: 99%
“…Illness‐associated metabolic changes and real or perceived barriers to initiating MNT in patients receiving ECMO may increase the risk for adverse clinical outcomes (Figure 1). The treatment of the underlying organ dysfunction is prioritized in clinical care and the implications of insufficient MNT often remains underrecognized 6–8 . Evidence derived from recent clinical studies and case reports indicate that adequate MNT, defined as achieving ≥80% of energy and protein goals, in patients receiving ECMO is possible 9 and associated with improvements in clinical outcomes 10–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation